Enabling simultaneous CO2 and water vapor removal by MOF-801/Pebax mixed matrix membranes: Molecular simulation and experimental study - Mahdi Ahmadi; Saravanan Janakiram; Sadiye Velioğlu; Arne Lindbråthen; Brian Arthur Grimes; Magne Hillestad; Liyuan Deng (Carbon Capture Science & Technology)
Dehydration and CO2 removal are two important gas separation processes. An efficient membrane enabling simultaneous reduction of water vapor and CO2 levels from humid gas streams, such as natural gas and power plant flue gas, may advance these processes. In this study, a water-harvesting metal-organic framework, MOF-801, was synthesized with an average particle size of 120 nm, which was then dispersed in a Pebax matrix to fabricate mixed matrix membranes (MMMs). The potential of the MOF-801 as a filler in MMMs was evaluated for water and CO2 separation from CO2/N2 and CO2/CH4 mixed gas streams. Compared with the neat Pebax membrane, 70% enhancement in the water permeability was achieved for an MMM of 20 wt.% MOF loading at 10 bar with a humid feed composition of CO2/CH4. A considerable CO2/N2 separation factor (108) and CO2 permeability (270 Barrer) were also obtained, exceeding the Robeson upper bound at both dry and humid states. A molecular simulation study was performed to reveal the adsorption sites in the MOF lattice and favorable interactions with gases. Interestingly, competition between gas components close to the Zr atom was observed, which is the favorable site for both CO2 and water. Competitive adsorption was found to be the dominating transport mechanism for the selective transport of CO2 and H2O in MOF-801, revealing the role of MOF-801 in MMMs for CO2 and water vapor separation under both humid and dry conditions.